Meningkatkan Kemudahan Pelanggan Kafe Melalui Pengembangan Sistem Manajemen Berbasis Web - Verdian, Armando; Riki, Riki (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
Today's technological developments have brought significant impacts to various industry sectors, including the café business. Café business owners face challenges in providing fast and efficient services to increase customer satisfaction. Many cafes still use manual ordering systems that can cause errors and slow down the service process. To overcome this problem, a web-based cafe management system was developed that aims to provide faster and more convenient service for customers and make it easier for managers to record and report daily transactions. The development method used in this research is prototype. The results show that this system is able to make the ordering and service process more efficient and optimal, even in crowded cafe conditions. In addition, this system helps cafe managers in recording and storing transaction data securely. This will eliminate the risk of data loss or damage that usually occurs in manual recording using books or paper.